REAL WORLD STUDY ON ORAL ESTRADIOL TREATMENT IN TRANSGENDER WOMEN - Sanyal, Debmalya; Mazumdar, Anirban; Chaudhuri, Soumyabrata Roy (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Treatment of transgender females (TGF) targets maintenance of physiological cisgender female hormone levels. This study evaluates dose effectiveness of oral estradiol valerate (EV) with (A) anti-androgens (spironolactone, finasteride), (B) post-orchiectomy or (C) GnRH-a/gonadotropin-releasing hormone agonists. METHODOLOGY We retrospectively evaluated Indian TGF on EV with (A), (B) or (C) with at least one year of follow-up. EV dose, changes in 17-β estradiol (E2) and testosterone (T) levels and achievement of target (E2>100 pg/ml; T<100 ng/dl) were assessed. RESULTS Overall cohort had 103 TGF: 41 were in group A, 22 were in group B, and 40 were in group C. In group A, 15% received spironolactone, 14 % received finasteride and 65% received both. Initial and final mean EV dose in overall cohort was 1.9 ± 0.58 mg and 3.22 ± 1.34 mg respectively, with significant increase in E2 (38.1 ± 21.1 to 92.7 ± 28.0 pg/ml) and decrease in T (587.2 ± 168.0 to 139.9 ± 164.1 ng/dl) from baseline. 32% of the overall cohort achieved target E2 levels and 56% achieved target T levels. Groups B and C required significantly lower (P<0.0001) final EV dose of 2.73 ± 0.88 mg and 2.6 ± 0.78 mg respectively, compared to 4.1 ± 1.5 mg in group A. Relatively, groups B and C had significantly higher final E2 (P=0.0016), lower final T (P<0.0001) and a significantly greater proportion of subjects achieving target hormone levels: E2 (22%(B), 45%(C) versus 10% (A) and T [(93%(B) 100%(C) versus 2%(A)]. CONCLUSIONS GnRH-a or orchiectomy, requiring significantly lower doses of EV, was more effective than anti-androgens in attaining target hormone levels in TGF. Spironolactone and finasteride did not help in testosterone suppression.